The people's hired guns? Experimentally testing the inclination of prosecutors to abuse the vague definition of crimes - Christoph Engel; Alicja Pluta (Max Planck Institute for Research on Collective Goods, 2011)
Legal realists expect prosecutors to be selfish. If they get the defendant convicted, this helps them advance their careers. If the odds of winning on the main charge are low, prosecutors have a second option. They can exploit the ambiguity of legal doctrine and charge the defendant for vaguely defined crimes, like conspiracy. We model the situation as a signalling game and test it experimentally. If we have participants play the naked game, at least a minority plays the game theoretic equilibrium and use the vague rule if a signal indicates that the defendant is guilty. This becomes even slightly more frequent if a misbehaving defendant imposes harm on a third participant. By contrast if we frame the situation as a court case, almost all prosecutors take the signal at face value and knowingly run the risk of loosing in court if the signal was false. Our experimental prosecutors behave like textbook legal idealists, and follow the urge of duty.
Keywords: D63; C72; K42; C91; D03; K14; 330; risk aversion; prosecution; doctrinal ambiguity; vaguely defined crimes; duty; DOSPERT; Justiz; Risikoaversion; Verhaltensökonomik; Test